Causal effects of lifetime smoking on breast and colorectal cancer risk: mendelian randomization study - Dimou, Niki; Yarmolinsky, James; Bouras, Emmanouil; Tsilidis, Konstantinos K.; Martin, Richard M.; Lewis, Sarah J.; Gram, Inger T.; Bakker, Marije F.; Brenner, Hermann; Figueiredo, Jane C.; Turzanski Fortner, Renée; Gruber, Stephen B.; et al. (Cancer epidemiology, biomarkers & prevention, 2021)
Background: Observational evidence has shown that smoking is a risk factor for breast and colorectal cancer. We used Mendelian randomization (MR) to examine causal associations between smoking and risks of breast and colorectal cancer. - Methods: Genome-Wide Association Study summary data were used to identify genetic variants associated with lifetime amount of smoking (n = 126 variants) and ever having smoked regularly (n = 112 variants). Using two-sample MR, we examined these variants in relation to incident breast (122,977 cases/105,974 controls) and colorectal cancer (52,775 cases/45,940 controls). - Results: In inverse-variance weighted models, a genetic predisposition to higher lifetime amount of smoking was positively associated with breast cancer risk [OR per 1-SD increment: 1.13; 95% confidence interval (CI): 1.00-1.26; P = 0.04]; although heterogeneity was observed. Similar associations were found for estrogen receptor-positive and estrogen receptor-negative tumors. Higher lifetime amount of smoking was positively associated with colorectal cancer (OR per 1-SD increment, 1.21; 95% CI, 1.04-1.40; P = 0.01), colon cancer (OR, 1.31; 95% CI, 1.11-1.55; P < 0.01), and rectal cancer (OR, 1.36; 95% CI, 1.07-1.73; P = 0.01). Ever having smoked regularly was not associated with risks of breast (OR, 1.01; 95% CI, 0.90-1.14; P = 0.85) or colorectal cancer (OR, 0.97; 95% CI, 0.86-1.10; P = 0.68). - Conclusions: These findings are consistent with prior observational evidence and support a causal role of higher lifetime smoking amount in the development of breast and colorectal cancer. - Impact: The results from this comprehensive MR analysis indicate that lifetime smoking is a causal risk factor for these common malignancies.
Gesehen am 03.11.2021